William Hogarth's family-pieces and his moral subjects: Relationships and interrelationships - Cowley, Robert LS (The British art journal, 2018)
George Vertue wrote about William Hogarth's burgeoning career as a fashionable painter. He muttered into his journal about 'the daily success of Mr Hogarth in painting small family pieces & Conversations with so much Air & agreeableness Causes him to be much followed, & esteemed, whereby he has much employment'. Overlapping this career as a portrait painter, Hogarth also established himself as a painter (and engraver) of what he was to call 'moder[n] moral Subject [s], an entirely different form of art'. He was boldly to claim that this was 'a Field unbroke up in any Country or any age'. Hogarth made a name for himself in a competitive market for the accuracy of his likenesses and the inclusion of clever, even impudent detail. The moral subjects that were to preoccupy Hogarth throughout his life are, to put it over simply, his works of fiction. This essay is a consideration of the possible interrelationship between Hogarth’s family pieces and pictures from within his famous progresses and other pictures. Hogarth’s early career as a painter of conversations and especially family pieces almost forced itself upon him as an influence on his other work as the author of moral fictions.